Analysis of Language Disorders in the Deaf: Literature Review of Factors, Patterns, and Intervention Strategies - Arista Widyawati; Kartika Kartika; Sujarwanto Sujarwanto (Universitas Negeri Malang, 2025)
Language disorders in deaf people include difficulties in phonological production, syntactic structure, and vocabulary mastery, which are rooted in auditory perception limitations. This study uses a literature review method to analyze various language learning approaches designed for deaf people. The results of the review indicate that deaf people often experience sound deviations such as insertion, omission, and substitution of vowels and consonants. In addition, they face difficulties in constructing simple and complex sentences due to limited exposure to spoken language patterns. Vocabulary mastery is also a major challenge due to minimal hearing experience, although visual-based learning media have proven effective in helping them understand and remember new words. The study also highlights the importance of pragmatic aspects in language, where deaf people often have difficulty adjusting language use to certain social contexts. Various learning methods, such as the use of visual media (BISINDO videos, magic trees), demonstration methods, and interactive learning models such as Make A Match, have been shown to improve the language skills of deaf people. In addition, family involvement and educator training are key elements in successful learning. In conclusion, effective learning interventions should include a holistic approach, which not only improves technical language skills, but also social skills. With innovative learning strategies and ongoing support from families, educators, and communities, deaf people have great potential to overcome their language barriers.